Experiments to investigate the effect of flight path on direct containment heating (DCH) in the Surtsey test facility - Allen, M.D.; Pilch, M.; Griffith, R.O. (Sandia National Labs., Albuquerque, NM (United States)); Nichols, R.T. (Ktech Corp., Albuquerque, NM (United States)) (U.S. Nuclear Regulatory Commission. Office of Nuclear Regulatory Research. Division of Systems Research., 1991)
The goal of the Limited Flight Path (LFP) test series was to investigate the effect of reactor subcompartment flight path length on direct containment heating (DCH). The test series consisted of eight experiments with nominal flight paths of 1, 2, or 8 m. A thermitically generated mixture of iron, chromium, and alumina simulated the corium melt of a severe reactor accident. After thermite ignition, superheated steam forcibly ejected the molten debris into a 1:10 linear scale the model of a dry reactor cavity. The blowdown steam entrained the molten debris and dispersed it into the Surtsey vessel. The vessel pressure, gas temperature, debris temperature, hydrogen produced by steam/metal reactions, debris velocity, mass dispersed into the Surtsey vessel, and debris particle size were measured for each experiment. The measured peak pressure for each experiment was normalized by the total amount of energy introduced into the Surtsey vessel; the normalized pressures increased with lengthened flight path. The debris temperature at the cavity exit was about 2320 K. Gas grab samples indicated that steam in the cavity reacted rapidly to form hydrogen, so the driving gas was a mixture of steam and hydrogen. These experiments indicate that debris may be trapped in reactor subcompartments and thus will not efficiently transfer heat to gas in the upper dome of a containment building. The effect of deentrainment by reactor subcompartments may significantly reduce the peak containment load in a severe reactor accident. 8 refs., 49 figs., 6 tabs.